Evaluating the effects of Melastoma malabathricum and Dicranopteris linearis as amendments for acid sulfate soil - Syazwan Sulaiman; Kathereen Liew (Soil Advances)
This study explores the potential of two underutilized plant materials, Melastoma malabathricum (MM) and Dicranopteris linearis (DL), to improve the fertility parameters of acid sulfate soil in a laboratory incubation. While the plant materials significantly increased soil pH (by 0.29 – 0.54 units), soil available P (by 3.17 – 4.75 mg kg−1), and exchangeable Ca (by 122.11 – 330.33 mg kg−1) whilst reducing exchangeable Al (by 2.19 – 4.58 cmol kg−1), these improvements were less pronounced relative to dolomite. Remarkably, at the lowest addition rate (20 t ha−1), both plant materials outperformed dolomite in reducing soil available Fe (end value of 227.88 – 165.00 mg kg−1 vs. 481.40 – 463.99 mg kg−1) and in improving soil available N with the incorporation of MM (end value of 10.51 mg kg−1 vs. 3.27 – 4.34 mg kg−1). Additionally, both plant materials consistently enhanced soil exchangeable K across all addition rates by up to an order of magnitude compared with dolomite (end value 52.87 – 174.53 mg kg−1 vs. 17.49 – 25.79 mg kg−1). Despite the generally less favourable results compared to dolomite, this study provides valuable insights into the limited body of information on the role of plant materials in altering the properties of acid sulfate soil.